Altering the Mechanical Load Environment During Growth Does Not Affect Adult Achilles Tendon Properties in an Avian Bipedal Model - Katugam, Kavya; Cox, Suzanne M.; Salzano, Matthew Q.; De Boef, Adam; Hast, Michael W.; Neuberger, Thomas; Ryan, Timothy M.; Piazza, Stephen J.; Rubenson, Jonas (Frontiers in Bioengineering and Biotechnology, 2020)
Tendon mechanical properties respond to altered load in adults, but how load history during growth affects adult tendon properties remains unclear. To address this question, we adopted an avian model in which we altered the mechanical load environment across the growth span. Animals were divided at two weeks of age into three groups: 1) an exercise control group given the opportunity to perform high-acceleration movements (EXE, n = 8); 2) a sedentary group restricted from high-intensity exercise (RES, n = 8); and 3) a sedentary group also restricted from high-intensity exercise and in which the gastrocnemius muscles were partially paralyzed using repeated bouts of botulinum toxin-A injections (RES-BTX, n = 8). Video analysis of bird movement confirmed the restrictions eliminated high-intensity exercise and did not alter time spent walking and sitting between groups. At skeletal maturity (33-35 weeks) animals were sacrificed for analysis, consisting of high-field MRI and material load testing, of both the entire free Achilles tendon and the tendon at the bone-tendon junction. Free tendon stiffness, modulus, and hysteresis were unaffected by variation in load environment. Further, the bone-tendon junction cross-sectional area, stress, and strain were also unaffected by variations in load environment. These results suggest that: a) a baseline level of low-intensity activity (standing and walking) may be sufficient to maintain tendon growth; and b) if this lower threshold of tendon load is met, tendon growth may override the load-induced mechanotransduction signal attributed to tendon remodeling in adults of the same species. These results are important for understanding of musculoskeletal function and tendon health in growing individuals.